N6-methyladenosine(m6A) demethylase FTO regulates cellular apoptosis following cobalt-induced oxidative stress. (15th March 2022) - Tang, Jianping; Su, Qianqian; Guo, Zhenkun; Zhou, Jinfu; Zheng, Fuli; Yu, Guangxia; Shao, Wenya; Hu, Hong; Wu, Siying; Li, Huangyuan
Abstract: Cobalt is an environmental toxicant that is known to damage human health. However, the molecular mechanisms underlying cobalt-induced neurotoxicity have not been elucidated in detail. In the present research, we used human neuroglioma H4 cells as an in vitro model. Cells were exposed to CoCl2 (0, 100, 200, 400 μM) for 24 h. We performed m 6 A sequencing techniques and constructed FTO-knockdown/FTO-overexpressing cells to investigate the role of FTO-mediated m 6 A modification in regulating apoptosis following CoCl2 induced oxidative stress. Our study has shown CoCl2 exposure led to the decrease of demethylase FTO as well as elevated oxidative stress. However, NAC treatment could partly reverse the reduction of FTO expression as well as the degree of ROS via eliminating oxidative stress. Meanwhile, MeRIP-seq and RNA-seq further revealed the potential function m 6 A modification in regulating apoptosis. More importantly, KEGG pathway and Gene ontology (GO) analyses further elucidated that the differentially m 6 A-modified genes were aggregated in apoptosis-related pathways. Mechanistic analysis indicated that knockdown of FTO facilitated CoCl2 -induced apoptosis via caspase activation and G1/S cell cycle arrest. Nevertheless, overexpression of FTO partly attenuated the increased apoptosis following CoCl2 exposure. More notably, we observed that FTO regulated apoptosis in an m 6 A-dependent manner. Therefore, our findings reveal that CoCl2 induced ROS affected the m 6 A modification of apoptosis-related genes by decreasing the expression of FTO, thereby resulting in the activation of apoptosis. These findings provide important insights into CoCl2 -induced apoptosis and m 6 A modification and propose a novel strategy for studying environmental toxicant-related neurodegeneration. Graphical abstract: Schematic representation of the role of the demethylase FTO-mediated m 6 A RNA methylation in apoptosis following CoCl2 induced oxidative stress. Image 1 Highlights: CoCl2 induced ROS affects m 6 A modification by targeting demethylase FTO. CoCl2 exposure promotes the activation of caspases to aggravate apoptosis. CoCl2 exposure results in G1/S cell cycle arrest. FTO modulates apoptosis in m 6 A manner following CoCl2 induced ROS.